High-Performance Liquid Chromatography-Diodic Array Detector, Fungistatic, and Anti-Morphogenical Analysis of Extracts from Psidium brownianum Mart. ex DC. Against Yeasts of the Genus Candida. Issue 8 (2nd August 2016) - Morais-Braga, Maria Flaviana B.; Carneiro, Joara N. P.; Machado, Antonio J. T.; Sales, Débora L.; Brito, Dara I.V.; Albuquerque, Rosimeire S.; Boligon, Aline A.; Athayde, Margareth L.; Calixto Júnior, João T.; Souza, Djair S. L.; Lima, Edeltrudes O.; Menezes, Irwin R. A.; et al.
Abstract : We assessed extracts from Psidium brownianum for antifungal activity and identified the phenolic phytocompounds. Minimum inhibitory concentration was determined by microdilution and IC50 was calculated. The minimun fungicidal concentration and the morphology of Candida were evaluated. Extracts analyzed by high-performance liquid chromatography demonstrated flavonoids and phenolic acids. The minimum inhibitory concentration was 8192 µg/mL and the IC50 varied between 1056 and 5128 µg/mL. Extracts showed fungistatic effect and altered the dimorphism of the strains, being the better result observed using the decoction, that affected the fungal dimorphism of the strain CA ATCC40006 at 4096 µg/mL.